Molecular Characterization of Classical Enterotoxin Genes among Staphylococcus aureus Isolates from Food Handlers in Baghdad City, Iraq - Obaid, Wael Adil (Iraqi Journal of Science, 2025)
Staphylococcus aureus (S. aureus) represents one of the most prevalent pathogens responsible for food poisoning because of its capacity for producing staphylococcal enterotoxin. The main goal of this investigation was to determine the presence of S. aureus and evaluate its enterotoxin genes in randomly selected food handlers from different restaurants and cafeterias in Baghdad City, Iraq. A total of 325 nasal swabs were collected from healthy food handlers and examined for the presence of S. aureus and classical enterotoxin genes. The strains were determined using confirmatory biochemical, morphological, and molecular (nuc gene) techniques. Five Staphylococcal enterotoxin genes, including sea, seb, sec, sed, and see, were screened using multiplex polymerase chain reaction. Out of the 325 samples, 30.15% harbored S. aureus pathogens that were confirmed by the existence of nuc gene in all isolates. 46.93% of isolates were positive for one or more classical genes. 22.44% of these isolates harbored a single enterotoxin gene. The prevalent single gene was sea (9.1%), followed by seb (6.1%), sec (4%) and lastly, sed (3%). The see gene was not observed in any of the isolates. 14 (14.28%), 6 (6.1%) and 4 (4%) exhibited two, three, or four genes, respectively. The sea + seb (5.1%) and sea + sec (4%) were the most frequent combinations. The current data conclusively demonstrated a high rate of enterotoxigenic S. aureus nasal carriage among the food handlers studied. Thus, comprehensive and continual evaluation of hygienic protocols and infection prevention plans is strongly recommended. Finally, nasal decolonization could be one of the most effective ways to minimize staphylococcal food poisoning and protect restaurant customers.